Corporate Governance Practices in Transportation and Logistics Companies during the COVID-19 Pandemic - Nugraha, Maulana; Suryani, Suryani; Nst, Chyntia Juliani (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
The purpose of this study is to leverage and strengthen corporate governance during this pandemic, including advocating for best practice COVID disaster recovery plans, developing emergency response checklists, establishing efficient disaster responses, and strengthening monitoring mechanisms for employees, operations, finance, customers, and supply chain. Calculation of data using descriptive exploratory quantitative methods using literature studies, namely analysis of real conditions that occur at this time and secondary data in the form of articles, news, and research results from several national and international research institutions. and regional is very important because while some regions of the world have excellent logistical opportunities that contribute to their success, other regions on the other hand do not have these characteristics.